Initial public offerings in Singapore - empirical study on risk characteristics and underpricing - Goh, Phyllis Pey Yin (2015)
Risk is a vital element in any investments. It comprises of both systematic and unsystematic risks. A prominent study of beta (B) as a measure of systematic risk of Initial Public Offerings (IPOs) in the United States was done by Ibbotson (1975). The first section of this study explores the trend of B of unseasoned issues in Singapore over their first 12 months after listing using the methodology of lbbotson (1975). The trend of total risks over the same period as measured by standard deviation and the high-low estimate of volatility of returns are also studied for comparison. Declining trends are observed in both B risk and total risks The underpricing of IPOs is not a new phenomenon. Indeed, there is well documented evidence that new issues are on average underpriced, that is, the offering . price is lower than the initial market price. The second section of the study tests on the relationship between the degree of underpricing and 7 issue-related variables. The empirical results suggest that IPOs are highly underpriced whenever the issues are heavily oversubscribed and the fractional interests retained are low. The relationships between the degree of underpricing and the rest of the issue-related factors are statistically insignificant.